Desain Kolam Retensi Tobuuha Dengan Aplikasi Storm Water Management Model (Swmm) Di Kelurahan Tobuuha Kecamatan Puuwatu Kota Kendari - Faisal, Laode Muhammad; Sukri, Ahmad Syarif; Mangidi, Uniadi; Bafadal, Ishak (Universitas Sulawesi Tenggara, 2024)
Tobuuha Village, Puuwatu District, Kendari City was previously a green open area which was naturally used for water absorption. However, this area has now changed its function to become a densely populated residential area, resulting in a significant reduction in water absorption. As a result, when it rains, surface flow becomes greater and causes puddles downstream. The aim of this research is to model the Tobuuha retention pond using the SWMM application for environmental changes that occur. Primary data collection was carried out by observing existing conditions and measuring the dimensions of channels and ponds around the retention pond. Meanwhile, secondary data was obtained from related agencies. The results of the research show that the flood discharge that will enter the retention pond is Q5 = 0.559 m3/second with the volume of water that enters and must be accommodated in the retention pond of 4577.0934 m3, while the existing capacity of the retention pond is 6978.44 m3, so it is considered still able to reduce flooding downstream of the pond. Therefore, the city government's plan to expand and increase the depth of the pool is not necessary because it will reduce the open space around the pool. Handling potential flooding and inundation around the location can be done by adjusting the sliding door openings and modifying several channels, namely channels J51-J52, M62-M63, N71-N106, and U97-U101. The SWMM simulation results for the proposed solution show that the retention pond is effective enough to prevent flooding in the surrounding area